The development of the revised COPE 68 inventory with English and Slovak versions - Halamová, Júlia; Kanovský, Martin; Strnádelová, Bronislava; Baránková, Martina; Greškovičová, Katarína (Frontiers in Psychology, 2023)
Although there have been several attempts (Carver et al., 1989; Carver,1997) at improving the COPE Inventory, the factor structure of the instrument is still in dispute (e.g., Solberg et al., 2021). In addition, studies have shown low reliability coefficients for some of the first-order factors, with Mental Disengagement having the lowest factor loadings (Carver et al., 1989; Crașovan & Sava, 2013; Garanyan & Ivanov, 2010). In a recent study on the external validation of the instrument, two additional first-order factors were identified in the qualitative analysis (Halamová et al., 2022), namely Self-care and Care for Others. Based on these arguments we created the Revised COPE 68 Inventory, changing some of the problematic items in the first order factor Mental Disengagement and adding items for the two new factors (Self-care and Care for Others). We then tested its reliability and performed factor analyses on the first and second-order factorial structure. The data were collected through social media in two languages, English and Slovak, using convenience and snowball sampling techniques. The English sample contained 834 participants with mean age 25.27 years (SD = 8.467) and the Slovak sample comprised 1,425 participants with mean age 33 years (SD = 14.59). For the statistical analyses we used Exploratory Structural Equation Model (ESEM) analyses with target rotation and WLSMV, Exploratory and second-order confirmatory factor analysis with the scores of the COPE Inventory and EFA. The Revised COPE 68 inventory had a good fit for all 17 first-order factors in both languages, including for the new factors Self-care and Care for Others. It appears that the first-order factors form a three-factor solution in both samples, consisting of active coping, social-emotional coping and avoidant coping. The revised Mental Disengagement has better psychometric properties as well. The Revised COPE 68 inventory was found to be a reliable multidimensional instrument for measuring various coping strategies in both the English and Slovak language versions.